2012
DOI: 10.1080/03610926.2010.551453
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Designs for Stated Choice Experiments that Incorporate Position Effects

Abstract: Davidson and Beaver (1977) extended the Bradley-Terry model to incorporate the possible effect of position within a choice set on the choices made in paired comparisons experiments.In this paper we further extend the Davidson and Beaver result to choice sets of any size.Under a mild restriction we show that designs optimal for the multinomial logit model are still optimal when position effects are included in the model. We also show how designs balanced for carry-over effects of all orders can be used to const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is observed that eliminating respondent effects simultaneously controls the within-pair order effects (see, Goos and Großmann (2011) and Bush, Street, and Burgess (2012)). …”
Section: Preliminaries and The Model Incorporating Respondent Effectsmentioning
confidence: 99%
“…It is observed that eliminating respondent effects simultaneously controls the within-pair order effects (see, Goos and Großmann (2011) and Bush, Street, and Burgess (2012)). …”
Section: Preliminaries and The Model Incorporating Respondent Effectsmentioning
confidence: 99%